2020
DOI: 10.1038/s41467-020-16932-z
|View full text |Cite
|
Sign up to set email alerts
|

Highly parallel lab evolution reveals that epistasis can curb the evolution of antibiotic resistance

Abstract: Genetic perturbations that affect bacterial resistance to antibiotics have been characterized genome-wide, but how do such perturbations interact with subsequent evolutionary adaptation to the drug? Here, we show that strong epistasis between resistance mutations and systematically identified genes can be exploited to control spontaneous resistance evolution. We evolved hundreds of Escherichia coli K-12 mutant populations in parallel, using a robotic platform that tightly controls population size and selection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 94 publications
(143 reference statements)
3
64
0
Order By: Relevance
“…We allow for an arbitrary correlation between home and non-home fitness. This form of the JDFE is consistent with our current understanding of the structure of global epistasis (Kryazhimskiy et al, 2014;Johnson et al, 2019;Lukačišinová et al, 2020 In this model, it is possible to obtain analytical expressions for the expected fitness trajectories of the population X t , Y t in the home and non-home environments (see Materials and Methods). As expected, our theory quantitatively predicts the fitness trajectories obtained in stochastic SSWM simulations ( Figure 3E).…”
Section: The Population Genetics Of Pleiotropysupporting
confidence: 75%
“…We allow for an arbitrary correlation between home and non-home fitness. This form of the JDFE is consistent with our current understanding of the structure of global epistasis (Kryazhimskiy et al, 2014;Johnson et al, 2019;Lukačišinová et al, 2020 In this model, it is possible to obtain analytical expressions for the expected fitness trajectories of the population X t , Y t in the home and non-home environments (see Materials and Methods). As expected, our theory quantitatively predicts the fitness trajectories obtained in stochastic SSWM simulations ( Figure 3E).…”
Section: The Population Genetics Of Pleiotropysupporting
confidence: 75%
“…It is absolutely clear to us today that the antibiotic resistance of E. coli and some other bacteria involves a combination of different factors [ 87 , 88 ]. Research results indicate that E. coli exhibits the strongest resistance to the longest used and most commonly prescribed antibiotics [ 89 , 90 , 91 ]. This is exactly the case with sulfonamides, which were first used in humans around 1930s [ 92 ].…”
Section: Usage Of Antibiotics In Different Countries Of Eu Region mentioning
confidence: 99%
“…In addition, heterogeneity in efflux pump expression can predispose subsets of bacterial populations with elevated acrAB expression to mutation even prior to antibiotic treatment ( 34 ). Deletion of genes associated with efflux pumps, such as tolC , can also reduce evolvability under antibiotic exposure ( 35 ). Furthermore, a recent study in Staphylococcus aureus found that higher NorA pump levels increased evolvability and that addition of a pump inhibitor could prevent resistance evolution ( 36 ).…”
Section: Introductionmentioning
confidence: 99%